Determinants of the first derivative of doppler blood flow velocity in common carotid artery - H. , Zulaika; Noor Azmi, Azran Azhim; P. , Bagherpour; M. , Saleh; Y. , Kinouchi; F. , Ibrahim (2013)
The aim of this study is determine first derivative of blood flow velocity (FDBFV) in common carotid artery (CCA) inorder to evaluate cardiovascular functions. The extracted derivative features suggest the acceleration waves which able toprovide aging index (AGI) in the cardiovascular system. In the study, acceleration wave derived from FDBFV consist of a,b, c, d, eand fwaves. The waves of a, b, c, d, eand frepresent the initial positive, early negative, re-increasing, late redecreasing,diastolic positive waves and diastolic negative waves, respectively. The FDBFV waveforms of 227 healthyvolunteers are statistically analyzed in the study. As a result, AGI in FDBFV (r=0.727, p<0.0001) shows strong correlationand consistency as compared to the other previuos study. In particular, there are significant correlations between systolicblood pressure, gender and heart rate in f waves. We found that there are sensitive to blood pressure and unknown wavefreatures in CCA. In conclusion, FDBFV in CCA is an effective method to evaluate the vascular aging.